Making Halal Food in Processed Fish: From Traditional Knowledge to Fishermen’s Household Awareness in Producing Fish-Processed Halal Food - Darvina Soedarwo, Vina Salviana; Saati, Elfi Anis (KARSA Journal of Social and Islamic Culture, 2018)
The daily life of the fishermenâ€™s household in Lekok Pasuruan, East Java, Indonesia is still adopting traditional knowledge, especially in their activities in catchingÂ Â and processing fishes.Â This knowledge is inherited from generation to the next. However,Â at present they have started making entrepreneurial endeavors although the endeavors are still limited to producing processed fishes in the form of fried fishes that are sold in the nearest markets. The problem encountered by the fishermen community is the stagnation of their welfare due to their relatively low incomes. Therefore, it is necessary to studyÂ the problem and also to guide them in solving the problem. The method of this research isÂ a Participatory Action Research (PAR) and using Rapid Rural Apraisal (RRA) approach.Â The findings of the research is aÂ model for empowering the fishermenâ€™s household. This model is named integrative-participative modelÂ with entrepreneurial mindset approach.Â Â By usingÂ the model,Â the fishermenâ€™s household will be more aware of the weightiness of fish-processed food variations and halal certification for the product that may improve the consumersâ€™ interest in buying the products.